PENDIDIKAN KARAKTER MELALUI MODEL PEMBELAJARAN KREATIF BAGI SISWA SEKOLAH DASAR (STUDI DI SDN MENDUNGAN 2 YOGYAKARTA) - Dwi Wijayanti; Wachid Pratomo (Universitas Sarjanawiyata Tamansiswa, 2019)
The aim of this research is to describe and analyze the implementation of character education through a creative learning model at the elementary school. This research was conducted at Mendungan 2 State Elementary School in April-September 2018. The research used a qualitative method with a descriptive approach. The data collection techniques used were direct observation, in-depth interview, and documentation. The data analysis steps consist of data presentation; data reduction; and verification, whereas the data validity tests include internal validity; external validity; reliability and objectivity. The research results showed that character education in elementary schools has been conducted well, that is, performed through a creative learning method which includes PAKEM learning; contextual teaching and learning (CTL); cooperative learning; and problem based learning. The model was used in thematic teaching which includes religious teaching; civics education; natural science; social science; Indonesian language; health and physical education; art culture and skills education; and dance art. The character values introduced include religious values; love of reading; honesty; discipline; tolerance; hard work; creativity; independence; democracy; nationalism; social care; and environmental care.